Prevalence of tobacco use in individuals with severe mental illnesses, São Paulo, Brazil Prevalência de tabagismo em indivíduos com transtornos mentais graves, São Paulo, Brasil - Lilian R C Ratto; Paulo R Menezes; André Gulinelli (Universidade de São Paulo, 2007)
OBJECTIVE: To analyze the prevalence of cigarette smoking in individuals with severe mental illnesses in a large urban centre of a middle income country. METHODS: Cross-sectional study carried out in São Paulo. The sample (N=192) comprised individuals diagnosed with severe mental illnesses who had contact with public psychiatric care services from September to November 1997 and were aged between 18 and 65 years. Prevalence of daily tobacco smoking in the 12 months previous to the interview and characteristics associated were studied. RESULTS: Out of 192 subjects with severe mental illnesses interviewed, 115 (59.9%; 95% CI: 52.6%; 66.9%) reported smoking cigarettes on a daily basis. Male gender, marital status separated or widowed, irregular use of neuroleptic drugs and history of ten or more psychiatric admissions were independently associated with cigarette smoking. CONCLUSIONS: The prevalence of cigarette smoking in the present sample was higher than that found in the general Brazilian population. Mental care services should implement non-smoking policies and mental health providers need to help patients with severe mental illness who want to quit smoking. OBJETIVO: Analisar a prevalência de tabagismo em amostra de indivíduos com transtornos mentais graves em um grande centro urbano de um país emergente. MÉTODOS: Estudo transversal realizado no município de São Paulo. A amostra (N=192) foi composta por indivíduos com diagnóstico de transtorno mental grave que tiveram contato com serviços psiquiátricos do setor público de setembro a novembro de 1997 e tinham idade entre 18 e 65 anos. O uso diário de cigarro nos 12 meses anteriores à entrevista e as características associadas a esse consumo foram investigados. RESULTADOS: Dos 192 indivíduos com transtornos mentais graves entrevistados, 115 (59,9%; IC 95%: 52,6%;66,9%) referiram ter feito uso diário de cigarros. Ser do sexo masculino, ser separado ou viúvo, fazer uso irregular de neurolépticos e ter história de dez ou mais internações anteriores mostraram-se independentemente associados ao tabagismo. CONCLUSÕES: A prevalência de tabagismo na amostra de indivíduos com transtornos mentais graves foi maior que a encontrada na população geral brasileira. Serviços de saúde mental devem promover políticas anti-fumo e profissionais de saúde mental devem ajudar os portadores de transtornos mentais graves que desejarem parar de fumar.